Capacitação interprofissional em álcool e outras drogas, o que acontece depois que o curso acaba? Desafios e subsídios para a transformação do conhecimento em prática - Domingues, Liz Paola [UNIFESP] (2021)
The multifactorial basis and the diversity of problems related to alcohol and other drugs (AOD) use demand professionals from different areas to be well trained to identify and intervene early and integrated in related cases. Although several professional trainings have been offered in the area, the staff attending the training programs usually struggle to implement the course knowledge in their work routine. Objective: this study aimed to investigate difficulties and strategies related to the transformation of theoretical knowledge into professional practice after training processes on AOD, aiming to gather evidence that support adjustments that might optimize future training experiences. Methodology: A mixed methods study was developed, where the quantitative approach occurred longitudinally, centered on the 2nd edition of the CRR-DU assessment, and the qualitative approach occurred transversely in all stages of the research. Structured self-administered questionnaires and semi-structured individual interview techniques, focus groups and Learning Alliance groups were used. Specialists in AOD experienced in offering training (educators) and working professionals who have already participated in some training (students) participated in the study. Results: we verified convergence between the findings of the different stages of the research. The main outcomes perceived after trainings on AOD related to the awareness of the training participants to the topic, with an increased appreciation for the complexities involved in substance use, the reduction of stigma, and a change of perspective related to substance users and services. However, there are difficulties in implementing systemic changes in the services in which trained professionals are inserted. The main strategies to facilitate the transformation of theoretical knowledge into professional practice are the approximation of the theoretical content to the reality of the professionals' routine, the use of active methodologies in favor of the protagonism of the student in their significant learning process, the involvement of managers and service teams in the training processes, and the offer of post-course attendance to support the implementation of changes. The University can play an important role in facilitating Permanent Health Education (EPS) processes, and the university extension seems to offer the opportunity to bring services together in a sustainable way, independent of xix political questions. Final considerations: Professional training in AOD favors the increase of theoretical knowledge and awareness, however, they are not efficient to promote systemic practice transformation in the services. For this, it is recommended the involvement of managers and service teams in the training processes, and theoretical contents that reflect the reality of professionals. The University may act as a facilitator of the learning processes foreseen by EPS.